Surface frustrated Lewis pairs in titanium nitride enable gas phase heterogeneous CO2 photocatalysis - Zou, Yunjie; Mao, Chengliang; Xu, Mingkai; Xing, Chao; Wang, Ruizhao; Ozin, Geoffrey A.; Ling, Lan (Nature communications, 2024)
Gas-phase heterogeneous catalytic CO 2 hydrogenation to commodity chemicals and fuels via surface frustrated Lewis pairs is a growing focus of scientific and technological interest. Traditional gas-phase heterogeneous surface frustrated Lewis pair catalysts primarily involve metal oxide-hydroxides (MOH•••M). An avenue to improve the process performance metrics lies in replacing the Lewis base MOH with a stronger alternative; an intriguing example being the amine MNH 2 in metal nitrides. This study establishes a proof-of-concept that an amine-type photoactive surface frustrated Lewis pair (MNH 2 •••M) can be constructed in titanium nitride (TiN x O y ) when integrated with a nanoscale platinum spillover co-catalyst. This surface frustrated Lewis pair, comprising Ti-NH 2 as the Lewis base and low-valent Ti as the Lewis acid, facilitates the gas-phase light-assisted heterogeneous reverse water-gas shift reaction. The reaction proceeds via a surface-active carbamate intermediate, Ti-(H 2 N-COO)-Ti, whereby the synergism of Lewis acidic and Lewis basic sites endows it with superior performance indicators compared to TiN x O y alone, as well as conventional platinum supported metal oxides. Heterogeneous surface frustrated Lewis pairs catalysis have been predominantly focused on metal oxide hydroxides. This study instead explores a different chemical composition space by shifting from metal oxides to metal nitrides for CO 2 photoreduction.